The Story of Cattle Ranching - Arnold, Oren; Floherty, John J. Jr. (Hudson, New York Harvey House, Inc., 1968)
"Each year the average twelve-year-old pupil in most of the schools on the North American continent consumes twice his weight in meat, most of which is that rich red meat called "beef." This rich red meat is produced by that famous adventurer in fact and fiction---the American cowboy. In the urban world of today few people really know much about cowboys, except those they see on television. They do not realize that it is the cowboy, or the rancher, as he is often called, who is responsible for the breeding, feeding, and marketing of cows from which beef comes. The science of cattle ranching has become one of this country's most important industries. It is costly, competitive, complicated "Big Business." The Story of Cattle Ranching is full of drama, action, and excitement, as well as being extremely informative. The stories of many famous ranchers, including Will Rogers and even Lyndon B. Johnson, are included in Mr. Arnold's account. Legends and songs familiar to many robust Americans, as well as the humor typical of the range, contribute greatly to the understanding of the "buckaroo", who has created a unique personality and who has developed an importance in the American way of life that cannot be overestimated. The author tells the story of raising cattle with rare knowledge and understanding, since he, himself, was "born to the saddle." "OREN ARNOLD was born and reared on a ranch in Rusk County, Texas. He acquired his first horse when he was six years old; by the time he was twelve, he was branding, doctoring, feeding cattle, and riding herd with the other cowboys on his father's Big A ranch. At nineteen he entered Rice University at Houston. For two years he worked on newspapers, then began a free-lance writing career that has resulted in the sale of more than 2,000 articles to major of almost fifty published books. Mr. Arnold holds the honor of having been chosen "Man of the Year" in Phoenix, Arizona. He has also been awarded the Governor's....."
Includes Index
Keywords: Ranching -- Juvenile Literature; cowboys -- Juvenile Literature; beef cattle -- Juvenile Literature